Сьӧлыктэм сьӧлык: кузьмадёсъёс, веросъёс / Анатолий Перевозчиков - Перевозчиков Анатолий Аркадьевич (Удмуртия, 2017)
Экземпляры: 3 (20181220) / Инвентарный номер: 50188 / Цена: 150.00 / Авт.знак: П 27 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Удм)-44